Effect of Short Saffil Fibres and SIC Particles on Mechanical Properties of Magnesium Alloys - Zuzanka Trojanova; Zoltan Szaraz; V. Gartnerova (Communications - Scientific letters of the University of Zilina, 2009)
The high temperature mechanical behaviour of composites with the AZ91 and AS21 magnesium alloys matrix, reinforced with short Saffil fibres and SiC particles were investigated. Samples were deformed in compression in the temperature range from room temperature to 300 °C. The yield stress and the maximum stress of true stress-true strain curves decrease with increasing temperature. Light and electron microscopy were used for study of the microstructure of composites. Possible hardening and softening mechanisms are discussed. The increased dislocation density and the shear stress at reinforcing phase/matrix interfaces were found as the most important contributions to the strengthening.